USE OF REGULAR EXPRESSIONS AS TEMPLATES IN FORMATIVE AND SUMMATIVE OPEN ANSWER QUESTIONS - Oleg A. Sychev; Valeriy O. Streltsov (Открытое образование (Москва), 2016)
The article describes problems in automated students testing using open-form questions with substantial amount of correct answers. Authors propose using of regular expressions as correct answer patterns. The problem of automatic hint generation during training tests is examined as well. To resolve this problem authors propose a matching string generation method, extending partial match from learner’s attempt. It is possible to give next correct character and next correct lexeme hints. The paper describes a solution in the form of a question type plugin for the popular e-learning system Moodle.